2009
DOI: 10.1002/cphc.200800697
|View full text |Cite
|
Sign up to set email alerts
|

Combustion of CH4/H2/Air Mixtures in Catalytic Microreactors

Abstract: The combustion of CH(4)/H(2)/HC mixtures in a very small space represents an alternative, innovative way to produce thermal/electrical energy. Pd/NiCrO(4) catalysts are lined on SiC monoliths via in situ solution combustion synthesis (SCS), and the monoliths are then tested by feeding CH(4), H(2), and lean CH(4)/H(2) mixtures into a lab-scale test rig at an output thermal power of 7.6 MW(th) m(-3). In all cases, the combustion temperature shifts to values lower than those observed in non-catalytic combustion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The PCZ catalyst was previously studied for CH 4 combustion in domestic appliances, and for CH 4 /air and CH 4 /H 2 /air lean mixtures oxidation into small monoliths (microburners) , as an alternative method to produce contemporarily thermal and electrical energy . CeO 2 is a very promising catalyst thanks to the good capability of Ce in changing rapidly its oxidation number from the Ce 3+ to Ce 4+ state, with a consequent O 2 fast release from its lattice to the nearby species: this O 2 mobility was proven to assist Pd in surface O 2 bonding helping thus the oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…The PCZ catalyst was previously studied for CH 4 combustion in domestic appliances, and for CH 4 /air and CH 4 /H 2 /air lean mixtures oxidation into small monoliths (microburners) , as an alternative method to produce contemporarily thermal and electrical energy . CeO 2 is a very promising catalyst thanks to the good capability of Ce in changing rapidly its oxidation number from the Ce 3+ to Ce 4+ state, with a consequent O 2 fast release from its lattice to the nearby species: this O 2 mobility was proven to assist Pd in surface O 2 bonding helping thus the oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, catalyst systems composed of Pd, PdO, Pt and their mixtures on a variety of supports (for example, SnO 2 , ZrO 2 , Al 2 O 3 , CeO 2 , TiO 2 , CeO 2 –TiO 2 , ZrO 2 ‐δ‐Al 2 O 3 ) are mainly described for the catalytic combustion of mixtures of CH 4 /CO/H 2 or the individual components 14–22. For lean CH 4 /H 2 /air mixtures, Specchia et al 23 described the catalyst system Pd/NiCrO 4 on ceramic SiC monoliths. Deshpande und Madras 24 described Pd‐ and Pt‐CeO 2 ‐based catalysts for the combustion of off‐gases from fuel cell systems.…”
Section: Introductionmentioning
confidence: 99%
“…13 Similarly, a number of different groups have used flame-based synthesis methods to prepare Pd-based combination catalysts, 14,15 as well as supported Pd catalysts. [16][17][18][19][20][21][22] Solution-based methods have frequently used Pd organometallics to prepare Pd-rich nanoparticles that were used in situ to catalyze organic reactions. [23][24][25][26][27][28][29][30] Unsupported Pd particles have previously been shown to be effective combustion catalysts, in the gas phase, however, in those studies the particle generation and catalytic combustion were done separately.…”
Section: Introductionmentioning
confidence: 99%
“…For example Nasibulin et al have demonstrated nanoparticle synthesis using Cu(acac) 2 (copper(II) acetylacetonate) entrained in a N 2 /O 2 flow and passed through a flow tube reactor, whereupon the organic ligands were burned off, leaving behind a vapor of Cu, which then condensed to form copper oxide nanoparticles . Similarly, a number of different groups have used flame-based synthesis methods to prepare Pd-based combination catalysts, , as well as supported Pd catalysts. Solution-based methods have frequently used Pd organometallics to prepare Pd-rich nanoparticles that were used in situ to catalyze organic reactions. …”
Section: Introductionmentioning
confidence: 99%